Erythropoietin and Cancer: The Unintended Consequences of Anemia Correction - Debeljak, Nataša; Solár, Peter; Sytkowski, Arthur J. (Frontiers in Immunology, 2014)
Until 1990, erythropoietin (EPO) was considered to have a single biological purpose and action, the stimulation of red blood cell growth and differentiation. Slowly, scientific and medical opinion evolved, beginning with the discovery of an effect on endothelial cell growth in vitro and the identification of EPO receptors (EPORs) on neuronal cells. We now know that EPO is a pleiotropic growth factor that exhibits an anti-apoptotic action on numerous cells and tissues, including malignant ones. In this article, we present a short discussion of EPO, receptors involved in EPO signal transduction, and their action on non-hematopoietic cells. This is followed by a more detailed presentation of both pre-clinical and clinical data that demonstrate EPO’s action on cancer cells, as well as tumor angiogenesis and lymphangiogenesis. Clinical trials with reported adverse effects of chronic erythropoiesis-stimulating agents (ESAs) treatment as well as clinical studies exploring the prognostic significance of EPO and EPOR expression in cancer patients are reviewed. Finally, we address the use of EPO and other ESAs in cancer patients.